Meunasah : Lembaga Pendidikan Islam Tradisional Aceh - Muslim Hasballah (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2020)
Meunasah is one of the basic levels of traditional Islamic educational institutions in Aceh. Which to date continues to be vehement with recitation and other civic activities. aims to find out the origins and the development of meunasah as a basic traditional Islamic educational institution in Aceh. This research applied a literature study by collecting various references. The results showed that meunasah had existed since the formation of the Islamic community in Aceh. The development of meunasah as a traditional Aceh Islamic education institution was only discovered during the period of Sultan Iskandar Muda (1607-1636).